2021
DOI: 10.1126/science.abb3363
|View full text |Cite
|
Sign up to set email alerts
|

Cygnus X-1 contains a 21–solar mass black hole—Implications for massive star winds

Abstract: The evolution of massive stars is influenced by the mass lost to stellar winds over their lifetimes. These winds limit the masses of the stellar remnants (such as black holes) that the stars ultimately produce. We use radio astrometry to refine the distance to the black hole X-ray binary Cygnus X-1, which we find to be 2.22−0.17+0.18 kiloparsecs. When combined with archival optical data, this implies a black hole mass of 21.2 ± 2.2 solar masses, higher than previous measurements. The formation of such a high-m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
165
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(184 citation statements)
references
References 107 publications
19
165
0
Order By: Relevance
“…• and q = 𝑀 1 /𝑀 2 = 0.45 +0.14 −0.07 ) are also shown as corner plots in Figure 6, confirming the detection of a 11.1 +2.1 −2.4 𝑀 BH orbiting a MSTO star in NGC 1850. If the inclination of the system is indeed confirmed by further studies, this represents one of the few massive BHs detected so far and its relative mass uncertainty of 20% (see Table 2) makes it one of the most accurate measurements available in the literature (Miller-Jones et al 2021).…”
Section: Light Curvesmentioning
confidence: 69%
“…• and q = 𝑀 1 /𝑀 2 = 0.45 +0.14 −0.07 ) are also shown as corner plots in Figure 6, confirming the detection of a 11.1 +2.1 −2.4 𝑀 BH orbiting a MSTO star in NGC 1850. If the inclination of the system is indeed confirmed by further studies, this represents one of the few massive BHs detected so far and its relative mass uncertainty of 20% (see Table 2) makes it one of the most accurate measurements available in the literature (Miller-Jones et al 2021).…”
Section: Light Curvesmentioning
confidence: 69%
“…Belczynski et al (2011) found that one such high-mass X-ray binary, Cygnus X-1, is expected to form an NSBH with a BH that carries near-maximal spin, although it would not merge within a Hubble time. However, following revised estimates of the component masses of Cygnus X-1 (Miller-Jones et al 2021 found that it will most likely form a BBH. Meanwhile, analyses of GWTC-1 and GWTC-2 have found evidence for BH spin (Abbott et al 2016f, 2021dVitale et al 2017a;Chatziioannou et al 2019;Kimball et al 2020), though they do not determine whether those BHs may have been formed with that spin.…”
Section: Spinsmentioning
confidence: 99%
“…In a way, turbulence may be the key factor for solving the issue, although it creates artifacts in the SN II and compact object formation landscapes. We stress, however, that the C20 model leads to low mass BHs of 10 M , especially for high α Λ values, which is not consistent with the BH masses in some Galactic BH X-ray binaries (e.g., Miller-Jones et al 2021).…”
Section: Resultsmentioning
confidence: 70%